2017
DOI: 10.1017/s0033291717002689
|View full text |Cite
|
Sign up to set email alerts
|

Brain-relevant antibodies in first-episode psychosis: a matched case–control study

Abstract: Abstract:There has been much recent excitement about the possibility that some cases of psychosis may be wholly due to brain-reactive antibodies, with antibodies to N-Methyl-D-Aspartate receptor(NMDAR) and the voltage gated potassium channel(VGKC)-complex reported in a few patients with first episode psychosis(FEP). Methods Participants were recruited from psychiatric services in South London,UK, from 2009-2011 as part of the Genetics and Psychosis(GAP)study. We conducted a case control study to examine NMDAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Additionally, one study that screened for IgA and IgM antibodies was negative [27]. Finally, a few other studies that either screened for antibodies against the NR1a/NR2b receptor subunit [10, 31], NR2a/NR2b subunit [32], or non-specifically for both NR1 and NR2 subunits [33-36], have found seropositivity in a small percentage of patients. As only antibodies directed against the NR1 subunit are known to produce anti-NMDAR encephalitis, the clinical relevance of these findings remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, one study that screened for IgA and IgM antibodies was negative [27]. Finally, a few other studies that either screened for antibodies against the NR1a/NR2b receptor subunit [10, 31], NR2a/NR2b subunit [32], or non-specifically for both NR1 and NR2 subunits [33-36], have found seropositivity in a small percentage of patients. As only antibodies directed against the NR1 subunit are known to produce anti-NMDAR encephalitis, the clinical relevance of these findings remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies that tested for IgG, IgA, or IgM anti-CASPR2 antibodies found seropositivity in a small percentage (2.5% or less) of patients [11, 15, 24, 29, 36], although numerous other studies were negative [16, 18, 20, 26, 28]. Of note, all of the positive studies that included a healthy control group, however, also found antibodies in a small number of controls (up to 2.9%), and no group differences were found [11, 15, 36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations